Cutaneous anthrax in adults: A review of 25 cases in the eastern Anatolian region of Turkey - Demirdag, K; Ozden, M; Saral, Y; Kalkan, A; Kilic, SS; Ozdarendeli, A (Springer Heidelberg, 2003)
Background: The clinical features, therapy and outcome of anthrax cases from the Elazig province (the eastern Anatolian region) of Turkey seen in our clinic over an 8-year period were reviewed. Patients and Methods: The records of 25 anthrax cases observed in our clinic during the period January 1994 to April 2002 were examined. Results: ALL cases were cutaneous; 18 (72%) patients exhibited malignant pustules and seven (28%) malignant edema. Three of the patients with a malignant pustule developed anthrax sepsis when admitted to our clinic. ALL cases were treated with penicillin. One patient who had penicillin allergy was treated with ciprofloxacin. In addition, patients with malignant edema were also treated with systemic corticosteroids (methylprednisolone or dexamethasone). Two patients died due to anthrax sepsis; one case with anthrax sepsis recovered. The mortality rate was 8%. Discussion: Anthrax is still a reality in Turkey. Cutaneous anthrax should be considered in any patient with a painless ulcer with vesicles, edema and a history of exposure to animals or animal products. In our series, penicillin and ciprofloxacin were effective in treatment of anthrax. Our anthrax sepsis case demonstrates that anthrax sepsis is not always fatal if antibiotic treatment is given early after diagnosis.
Keywords: Oral-Oropharyngeal Anthrax; Outbreak